Investigation of continuous adsorption of Pb(II), As(III), Cd(II), and Cr(VI) using a mixture of magnetic graphite oxide and sand as a medium in a fixed-bed column. Issue 4 (August 2018) - Ghasemabadi, Seyedehleila Mohammadipour; Baghdadi, Majid; Safari, Edwin; Ghazban, Fereydoun
Abstract: In this research, the removal of Cr(VI), Pb(II), As(III), and Cd(II) was studied by a medium containing a mixture of magnetic graphene oxide (MGO) and sand with the grain size in the range of 100–500 μm. GO and MGO were synthesized and characterized by SEM, XRD, BET, VSM, and FT-IR analysis. Fixed-bed and batch studies were conducted to assess the performance of the MGO for the removal of heavy metals from the aqueous phase. The batch adsorption equilibrium data were investigated by UT, Langmuir, Temkin, Radke-Prausnitz, Dubinin-Radushkevich, Redlich-Peterson, and Freundlich models. Adsorption isotherms of all investigated adsorbates were consistent with the UT, Redlich-Peterson, Radke-Prausnitz, and Langmuir models. The maximum adsorption capacities were 0.608, 0.272, 0.300, and 0.484 mmol g −1 for Pb(II), As(III), and Cd(II), and Cr(VI), respectively. Desorption constants of 0.00, 0.0126, 0.041, and 0.312 mmol L −1 were obtained for Pb(II), As(III), and Cd(II), and Cr(VI), respectively. Furthermore, column experiments were modeled by Thomas and Adam's-Bohart models. The experimental data were well fitted using the Thomas model, and the adsorption capacities were 0.189, 0.10, 0.086, and 0.056 mmol g −1 for Pb(II), As(III), and Cd(II), and Cr(VI), respectively. The volume of the treated influent containing Pb (II) was much higher than that of the influent containing other elements under the same condition. The results of fixed-bed experiments showed that the proposed media was efficient in removing of Pb(II) due to the low desorption constant and high adsorption capacity. Desorption study results showed that the MGO could be reused efficiently.